2005
DOI: 10.1093/jnen/64.5.420
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathologic, Biochemical, and Molecular Characterization of the Frontotemporal Dementias

Abstract: The frontotemporal dementias (FTDs) are a heterogeneous group of neurodegenerative disorders that are characterized clinically by dementia, personality changes, language impairment, and occasionally extrapyramidal movement disorders. Historically, the diagnosis and classification of FTDs has been fraught with difficulties, especially with regard to establishing a consensus on the neuropathologic diagnosis. Recently, an international group of scientists participated in a consensus conference to develop such neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 51 publications
2
53
0
Order By: Relevance
“…23 An association between the fluent aphasic clinical form of FTD (but not other clinical FTD forms) and APOE 4 was found by Short et al 24 Recently, the APOE 4 allele has been found to be overrepresented in clinical FTD within a homogenous population in southern Italy, 14 and in neuropathologically-verified Pick's disease and dementia lacking distinctive histopathology (DLDH). 25 Tau pathology is characteristic of frontotemporal dementia associated with mutations in the MAPT gene on chromosome 17, and in a considerable proportion (40% in one series) of sporadic cases. 26 However, many other cases of FTD, e.g.…”
Section: Discussionmentioning
confidence: 94%
“…23 An association between the fluent aphasic clinical form of FTD (but not other clinical FTD forms) and APOE 4 was found by Short et al 24 Recently, the APOE 4 allele has been found to be overrepresented in clinical FTD within a homogenous population in southern Italy, 14 and in neuropathologically-verified Pick's disease and dementia lacking distinctive histopathology (DLDH). 25 Tau pathology is characteristic of frontotemporal dementia associated with mutations in the MAPT gene on chromosome 17, and in a considerable proportion (40% in one series) of sporadic cases. 26 However, many other cases of FTD, e.g.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, a direct interaction between tau and TDP-43 seems unlikely but needs to be investigated in more biochemical detail. In addition, the absence of TDP-43 pathology in PSP, a tauopathy that shares clinical, biochemical, pathologic, and genetic similarities with CBD (33,34), also argues against a simple relationship between tau dysfunction and TDP-43 accumulation.…”
Section: Tar-dna-binding Protein 43 Was Recently Identified As a Disementioning
confidence: 99%
“…In the mid-1980s, tau was identified to be the principal component of neurofibrillary lesions in the AD (34,38,39). Similar lesions were also found in other neurodegenerative diseases including corticobasal degeneration (40), amyotrophic lateral sclerosis/parkinsonism dementia complex of Guam (41,42), Down syndrome (43), progressive supranuclear palsy, Pick's disease, argyrophilic degeneration (reviewed by 7), myotonic dystrophy (44), and the family of fronto-temporal dementias (FTD) (45). AD is a special form of tauopathy additionally characterised by extra-cellular deposits of A_ and amyloid deposits in cerebral blood vessels (46).…”
Section: Intra-and Extra-cellular Protein Inclusionsmentioning
confidence: 85%